IMPLEMENTASI PEMBELAJARAN AQIDAH AKHLAK DALAM PENGUATAN KESEHATAN MENTAL SISWA : STUDI KASUS DI MIM NGLARAN I - Risma Mega Utami; Ismail (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: Indications of suboptimal mental health of students at MIM Nglaran I and the lack of systematic integration of spiritual values ​​into learning are the background of this research. Students show a tendency to experience anxiety, stress, difficulty managing emotions, and aggressive behavior in social interactions. This study aims to analyze the implementation of Aqidah Akhlak learning in strengthening mental health, identify the strategies implemented, and understand their contribution to emotional regulation and psychological resilience of students. This study used a descriptive qualitative approach with a case study design. Subjects included sixth-grade students, Aqidah Akhlak teachers, and the madrasah principal. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through reduction, presentation, and drawing conclusions with triangulation to ensure validity. The results indicate that teacher role models, religious habits, and religious activities contribute to increased self-confidence, emotional regulation, empathy, and the ability to manage anxiety. However, their effectiveness is influenced by the consistency of implementation and support from the school. Abstrak: Indikasi kurang optimalnya kesehatan mental siswa di MIM Nglaran I serta belum terintegrasinya nilai-nilai spiritual secara sistematis dalam pembelajaran menjadi latar belakang penelitian ini. Siswa menunjukkan kecenderungan mengalami kecemasan, stres, kesulitan mengelola emosi, dan perilaku agresif dalam interaksi sosial. Penelitian ini bertujuan menganalisis implementasi pembelajaran Aqidah Akhlak dalam penguatan kesehatan mental, mengidentifikasi strategi yang diterapkan, serta memahami kontribusinya terhadap regulasi emosi dan ketahanan psikologis siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Subjek meliputi siswa kelas VI, guru Aqidah Akhlak, dan kepala madrasah. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan dengan triangulasi untuk menjamin keabsahan. Hasil menunjukkan bahwa keteladanan guru, pembiasaan religius, dan kegiatan keagamaan berkontribusi pada peningkatan kepercayaan diri, regulasi emosi, empati, serta kemampuan mengelola kecemasan. Namun, efektivitasnya dipengaruhi konsistensi pelaksanaan dan dukungan dari sekolah.